GenEx: A Simple Generator Structure for Exclusive Processes in High Energy Collisions (Communications in Computational Physics, 2018)
A simple C++ class structure for construction of a Monte Carlo event generatorwhich can produce unweighted events within relativistic phase space is presented.The generator is self-adapting to the provided matrix element and acceptance cuts. Theprogram is designed specially for exclusive processes and includes, as an example ofsuch an application, implementation of the model for exclusive production of mesonpairs $pp$→ $p$$M^+$$M^−$$p$ in high energy proton-proton collisions.